Faktor-faktor Yang Berhubungan Dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil Di Rumah Sakit BhayangkaraTahun 2023 - Sesilia Triana Dewi; Shella, Theresia Shella Beredikta (STIKes Budi Mulia Sriwijaya, 2024)
ABSTRACT Hyperemesis gravidarum is an excessive nausea and vomiting during pregnancy that interferes with daily work. This study aimed to find out the relationship among gravida, hydatidiform mole and multiple pregnancy simultaneously and the incidence of HEG in pregnant women in Bhayangkara hospital of Palembang. This study used analytical survey method. The population in this study was all pregnant women visiting the hospital from January to December 2018. The number of samples was 79 respondents taken using total population. The results showed that 18 respondents (22,8%) were primigravida and 61 respondents (77,2%) were multigravida; 8 respondents (10,1%) experienced hydatidiform mole but 71% respondents (89,9%) did not experience it; 7 respondents (8,9%) experienced multiple pregnancy but 72 respondents (91,9%) did not experience it. Based on chi-square statistical test results, it was concluded simultaneously that there was a meaningful relationship between HEG and gravida, between HEG and hydatidiform mole and between HEG and multiple pregnancy with p value of 0.015 < α 0.05, 0.026 < α 0.05, and 0.007 < α 0.05 respectively. It is expected that all pregnant women always seek information about pregnancy complications, especially hyperemesis gravidarum.